1983
DOI: 10.1111/j.1600-0536.1983.tb04622.x
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxicity of Heracleum laciniatum

Abstract: Phytophotodermatitis from Heracleum laciniatum is described in 2 typical cases. Experimental phytophotodermatitis was produced using homogenates from leaves of the plant and long-wave ultraviolet light. The homogenates of leaves produced strong phototoxic reactions. The minimal phototoxic erythema dose was determined to be lowest for abdominal and midback skin. The action spectrum for Heracleum laciniatum homogenates applied topically was found to be in the range 315-375 nm with peak sensitivity at 330-335 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…More than 150 compounds have been isolated from plants mainly belonging to the families of Rutaceae and Umbelliferae, comprising common edible vegetables and fruits such as lemons, oranges, and grapefruits [184,185]. Phototoxic furocoumarins such as xanthotoxin (8-MOP) or bergapten have been isolated from the Umbelliferae, Moraceae, Leguminosae, Rosaceae, and Compositae plant families [186]. The photoreactivity of the plants depends on their furocoumarins (psoralens) content.…”
Section: Terrestrial Cyclobutane-containing Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 150 compounds have been isolated from plants mainly belonging to the families of Rutaceae and Umbelliferae, comprising common edible vegetables and fruits such as lemons, oranges, and grapefruits [184,185]. Phototoxic furocoumarins such as xanthotoxin (8-MOP) or bergapten have been isolated from the Umbelliferae, Moraceae, Leguminosae, Rosaceae, and Compositae plant families [186]. The photoreactivity of the plants depends on their furocoumarins (psoralens) content.…”
Section: Terrestrial Cyclobutane-containing Alkaloidsmentioning
confidence: 99%
“…Their structures are shown in Fig. 56 (185)(186)(187)(188) Antidepolarizing agents anatruxonium (199), truxillonium (200), pyrocyclonium (201), and cyclobutonium (202) have been synthesized and their biological activities reported [261][262][263]. In rabbits, cats, chicks, and guinea pigs, the four compounds possess high curarelike properties.…”
Section: Synthetic Analogs Of Natural Alkaloids With Cyclobutane Ringmentioning
confidence: 99%
“…The usage of oral khella as a therapy is not as safe as it might sound and limited by its potential cytotoxicity. [24][25][26][27][28] In humans, two studies have been conducted; the first investigated the utilization of oral khellin to reduce blood lipids and the second studiedthe effects of khellin in vitiligo. 24,25 Researchers observed that gastro-intestinal side-effects were observed frequently (29% of patients in the vitiligo study) and, elevated aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were also reported during therapy (7% to 14%).…”
Section: Discussionmentioning
confidence: 99%
“…The furocoumarins (psoralens) found in khella plant may cause photosensitization and dermatitis. 26 One study reported fourirritant active ingredients from khella seeds and investigatedthe mechanism of action of their potential contact dermatitis. 28 A case report described a case withallergic rhinitis and contact urticaria as a result of exposure to khella during cultivation in a florist shop.…”
Section: Discussionmentioning
confidence: 99%
“…It was responsible of a dermal-epidermal cleavage, leading to apparition of vesicles and bullae. Two other cases of phytophotodermatitis by using Ammi majus L. were reported in literature [1][2][3][4]. Other authors described cases of urticaria, allergic rhinitis and ocular toxicity after the use of this plant [5].…”
mentioning
confidence: 99%